Green Supply Chain Management Practices in Malaysia Manufacturing Industry - Veera Pandiyan Kaliani Sundram; Atikah Shamsul Bahrin; Akmal Aini Othman; Zarina Abdul Munir (International Journal of Supply Chain Management, 2017)
The purpose of this study is to determine the relationship between green supply chain management practices towards environmental and operational performances among Malaysian manufacturing firms. The research design for this study employs quantitative method using survey questionnaires which was developed based on a thorough review of relevant literature on green practices. A total of 300 questionnaires were distributed randomly among the manufacturing firms in Malaysia. A total of 7 variables included in this study, comprising green purchasing, investment recovery, eco-design and packaging, reverse logistic, and cooperation with customers, manufacturing environmental and operational performance. This study will measure the impact between green supply chain management practices towards environmental and operational performance in Malaysian manufacturing industry.